Torque-bias profile for improved tracking of the Deep Space Network antennas. - Gawronski, W. (IEEE Antennas & propagation magazine.)
Measurements at the drives of the NASA Deep Space Network (DSN) antennas indicated that the small gap between gear teeth was causing backlash at the gearboxes and elevation bullgear. Left uncorrected, backlash will deteriorate the antenna's pointing precision. At DSN, the backlash was eliminated by implementing two identical drives that impose two nonidentical torques (a.k.a. torque bias, or counter-torque). The difference between these two torques depends on the antenna load, and is shaped by the drive's electronic circuits. The paper explains the shaping principles of the circuit, and shows how the circuits can be modified to improve the antenna dynamics under external disturbances.